Relationship between Training Intensity and Doctor’s Job Satisfaction at Primary Health Care in Indonesian - Purnamasari, Gita; Misnaniarti, Misnaniarti (Jurnal Midpro, 2020)
A doctor’s job satisfaction is important because it will improve the quality of health services. This study aimed to determine the relationship between intensity training and doctors satisfaction. This research was a cross-sectional study using data from Risnakes 2017. The sample was 5,140 doctors primary health care with civil servant status in Indonesia that was randomly selected. The data were analyzed using the Spearman correlation. This study showed that mean job satisfaction was 70.07 and intensity of the training was 3.98. There is a positive correlation between the training intensityand the doctor's job satisfaction of primary health care in Indonesia (p-value <0.000 and r = 0.063). More doctor's training will improve the ability of doctors to care for the patient's clinical according to the standards of competence.